UPAYA GURU SEKOLAH DASAR DALAM MENCIPTAKAN PENGELOLAAN KELAS YANG KONDUSIF DI KELAS V SD MUHAMMADIYAH 1 LIMBOTO - Sela Marselia Harun; Yurni Rahman; Yane Hardiyanti Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the efforts undertaken by Grade V teachers in establishing a conducive classroom management system, with a primary focus on elucidating the specific strategies employed to cultivate a supportive learning environment. The research was designed to contribute to the enhancement of aducators’ classroom management compentencies. A qualitative approach utilizing a case study design was employed. Data were ghatered through classroom observation, semi-structured interviews, and document analysis. The research subjects comprised the school principal, the Grade V homeroom teacher, and Grade V students. Data analysis wasconducted using a systematic procedure encompassing data reduction, data presentation, and conclusion drawing. The findings indicated that the teacher’s efforts to foster a conducive classroom environment were operationalized across five key indicators: interpersonal communication competence, the cultivation of positive teacher-student relationships, the capacity to comprehend and address students’ emotional needs, proficiency in delivering social support and academic motivation, and the ability to regulate peer interactions and mediate classroom conflicts. The majority of these indicators were effectively implemented. However, certain dimensions necessitated further refinement, particurlarly concerning the management of social interactions and conflict resolution within the classroom. Consequently, it was concluded that the elementary school teacher’s initiatives in estabilishing conducive classroom management in Grade V at SD Muhammadiyah 1 Limboto were substantially well-executed.